Genomic analyses of Bacteroides fragilis: subdivisions I and II represent distinct species - English, Jamie; Newberry, Fiona; Hoyles, Lesley; Patrick, Sheila; Stewart, Linda (Journal of medical microbiology, 2023)
Introduction. Bacteroides fragilis is a Gram-negative anaerobe that is a member of the human gastrointestinal microbiota and is frequently found as an extra-intestinal opportunistic pathogen. B. fragilis comprises two distinct groups – divisions I and II – characterized by the presence/absence of genes [ cepA and ccrA ( cfiA ), respectively] that confer resistance to β-lactam antibiotics by either serine or metallo-β-lactamase production. No large-scale analyses of publicly available B. fragilis sequence data have been undertaken, and the resistome of the species remains poorly defined. Hypothesis/Gap Statement. Reclassification of divisions I and II B. fragilis as two distinct species has been proposed but additional evidence is required. Aims . To investigate the genomic diversity of GenBank B. fragilis genomes and establish the prevalence of division I and II strains among publicly available B. fragilis genomes, and to generate further evidence to demonstrate that B. fragilis division I and II strains represent distinct genomospecies. Methodology . High-quality ( n =377) genomes listed as B. fragilis in GenBank were included in pangenome and functional analyses. Genome data were also subject to resistome profiling using The Comprehensive Antibiotic Resistance Database. Results. Average nucleotide identity and phylogenetic analyses showed B. fragilis divisions I and II represent distinct species: B. fragilis sensu stricto ( n =275 genomes) and B. fragilis A ( n =102 genomes; Genome Taxonomy Database designation), respectively. Exploration of the pangenome of B. fragilis sensu stricto and B. fragilis A revealed separation of the two species at the core and accessory gene levels. Conclusion . The findings indicate that B. fragilis A, previously referred to as division II B. fragilis , is an individual species and distinct from B. fragilis sensu stricto . The B. fragilis pangenome analysis supported previous genomic, phylogenetic and resistome screening analyses collectively reinforcing that divisions I and II are two separate species. In addition, it was confirmed that differences in the accessory genes of B. fragilis divisions I and II are primarily associated with carbohydrate metabolism and suggest that differences other than antimicrobial resistance could also be used to distinguish between these two species.